2014
DOI: 10.1155/2014/156020
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Stress Signaling Promotes Cellular Adaptations

Abstract: Mitochondrial dysfunction has been implicated in the aetiology of many complex diseases, as well as the ageing process. Much of the research on mitochondrial dysfunction has focused on how mitochondrial damage may potentiate pathological phenotypes. The purpose of this review is to draw attention to the less well-studied mechanisms by which the cell adapts to mitochondrial perturbations. This involves communication of stress to the cell and successful induction of quality control responses, which include mitop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 136 publications
3
51
0
1
Order By: Relevance
“…This result suggests that not only is nuclear DNA damage verification an important cell cycle checkpoint, but organellar DNA damage verification is as well. Because mitochondrial dysfunction is efficiently signaled to the nucleus (Van Aken et al, 2009;De Clercq et al, 2013), mitochondrial DNA stress is also likely to cause a retrograde signal affecting nuclear gene expression (Barbour and Turner, 2014) and to affect plant development as such. In animals, a mitochondrial damage checkpoint during the cell cycle has been proposed because mitochondrial dysfunction leads to cell cycle arrest, cellular senescence, and tumorigenic phenotype (reviewed in Singh, 2006;van Gisbergen et al, 2015).…”
Section: Importance Of Mitochondrial Proteins In Plant Growthmentioning
confidence: 99%
“…This result suggests that not only is nuclear DNA damage verification an important cell cycle checkpoint, but organellar DNA damage verification is as well. Because mitochondrial dysfunction is efficiently signaled to the nucleus (Van Aken et al, 2009;De Clercq et al, 2013), mitochondrial DNA stress is also likely to cause a retrograde signal affecting nuclear gene expression (Barbour and Turner, 2014) and to affect plant development as such. In animals, a mitochondrial damage checkpoint during the cell cycle has been proposed because mitochondrial dysfunction leads to cell cycle arrest, cellular senescence, and tumorigenic phenotype (reviewed in Singh, 2006;van Gisbergen et al, 2015).…”
Section: Importance Of Mitochondrial Proteins In Plant Growthmentioning
confidence: 99%
“…More fission leads to more fragmented and smaller mitochondria, which are easily detected as damaged mitochondria and are degraded by mitophagy. Lower mitochondrial membrane potential diminishes fusion and promotes fission and mitophagy [22]. Unbalanced fusion leads to mitochondrial elongation while unbalanced fission leads to excessive mitochondrial fragmentation, both of which can lead to impaired mitochondrial functions (Fig.…”
Section: Mitochondrial Fission Fusion and Autophagy (Mitophagy)mentioning
confidence: 99%
“…Fatty acids have a role in regulating the activity of MPT pore which links lipids with mitochondrial dysfunction as well as with mitochondrial degradation (Fig. 4) [22]. Mitophagy mediated by MPT pore can also be induced by Drp1 translocation from cytosol to mitochondria.…”
Section: Mitochondrial Fission Fusion and Autophagy (Mitophagy)mentioning
confidence: 99%
“…Multiple studies of preeclampsia and IUGR have shown increases in mitochondrial content [16,[19][20][21][22], indicating placental mitochondrial biogenesis is initiated in reaction to adverse conditions [23].…”
Section: Introductionmentioning
confidence: 99%